Une genre de nouvelle discrimination chromatique - R. J. Aeschlimann (Glad!)
A trend such as the red sneakers one is a pretext to distinguish between social classes. We could keep on imagining for every group of women and men a colour matching as much as possible what they aspire to be, and at the end, which could literally describe them. To prove that gender-neutral language [or inclusive writing] should be as multifarious as the possibilities of shoes' colour, this narrative distinguish between twelve types of non-heterosexist phrasing, made to measure to so many categories of persons.